Designing Tin and Hard Carbon Architecture for Stable Sodium‐Ion Battery Anode - Rana Faisal Shahzad; Shahid Rasul; Mohamed Mamlouk; Ian Brewis; Rana Abdul Shakoor; Abdul Wasy Zia (Small Structures)
The lack of anodes stability is one among key barriers to the widespread commercialization of sodium‐ion batteries (SIBs). This is attributed to graphite, a well‐known common anode material for a range of commercial batteries including lithium‐ion batteries (LIBs), which limits the insertion of sodium (Na) ions due to their large ionic size. Tin (Sn) has shown its potential as a suitable anode material because it exhibits high capacities in conversion and alloying reactions. However, it endures significant volumetric expansion and slower reaction rates during sodiation. To overcome these challenges, this work presents a novel anode material for SIBs where a 2D layered architecture of Sn with a hard carbon (HC) buffer layer is engineered using physical vapor deposition technique. This novel anode (SnHT/HC) exhibits a high initial capacity of 470 mAhg−1 and an exceptional retention of 438 mAhg−1 after 3000 cycles at 0.2C, with 99 % Coulombic efficiency. SnHT/HC testing at varying fast charge and discharge C‐rate of 5C, 10C, 15C, and 50C has shown promising results. Better electron transport and reduced volumetric changes are perceived to enhance the overall performance of SnHT/HC electrodes.